IMPACT OF THE EXISTENCE OF ETAWA BEACH GOAT FARM ON THE WELFARE OF THE COMMUNITY OF GAMPONG GEULINGGANG, LHOKSUKON DISTRICT, UTARA ACEH REGENCY - Nurlina Nurlina; Fadli Fadli; Eva Wardah (LPPM Universitas Malikussaleh - Indonesia, 2022)
Etawa goat breeding is one of the goat breeders business in Geulinggang Village, Sub District Lhoksukon, North Aceh district. The existence of breeds affect to welfare of society so researchers want to examine the effects of Etawa breeding on people's welfare. The purpose of this study was to find out (1) the negative and positive impact on the existence of Etawa breeders. (2) To what extent the involvement of the Etawa farmer in overcoming the negative impacts caused by goats in Gelinggang Village, Lhoksukon District. The research method was used quantitative descriptive method. From the results of this study there were two impacts felt by the Gampong Geulinggang community. (1) the positive impact are absorption of labor is 67% and the welfare level is better 72%